Madagascar : Back to the Future on the Road to Sustained and Balanced Growth, Country Economic Memorandum, Volume 2, Annexes - World Bank (Washington, DC, 2012)
The objective of this study is to accompany Malagasy authorities in their transition towards economic emergence. If the contribution of foreign capital and the abundance of natural resources should help the Malagasy economy escape from the poverty trap by increasing its domestic savings and investment capacities, as well as its technological capacities. International experience reminds us that this transition is far from being automatic. Indeed, there are more examples of countries that have failed than of those who have succeeded. The successes of Chile, Tunisia, Malaysia, Mauritius, and Botswana can inspire the Malagasy policy makers while showing them which economic policy choices become imperative. This study is divided into four parts. The first part begins with an analysis of Madagascar's economic performance, trying to recall its fragility in spite of the good results recorded over these last few years. This fragility will be highlighted through the relatively narrow basis of the economic growth that has greatly relied on foreign capital inflows, putting the need to follow an adequate foreign exchange management policy at the center of the agenda and, thus, minimize its possible negative impact on exports. The second part will focus on the issue of private sector promotion. Recent diagnoses of Madagascar's economy and the strategy adopted by Malagasy authorities (with the support of its development partners) have shown that to be sustained and shared out over time, economic growth will have to rely on a dynamic and competitive private sector. The third part is dedicated to sharing the fruits of economic growth by giving a special emphasis to the distribution of the benefits related to the large mining and tourism investment projects within the population. These large projects represent a unique opportunity for Madagascar's development but also undoubtedly a danger if they do not allow the emergence of spillover effects among the local businesses and labor force. Finally, the fourth and final part proposes an agenda of economic reforms. Ambition is not to formulate a patchy list of proposals, but rather to propose a series of options that will help address the issues of competitiveness and shared growth that are central to the success of the current strategy followed by the Malagasy authorities.